Tracing a Mantle Component in Both Paleo and Modern Fluids Along Seismogenic Faults of Southern Italy - Filippo Zummo; Fabrizio Agosta; Antonio M. Álvarez‐Valero; Andrea Billi; Dario Buttitta; Antonio Caracausi; Gabriele Carnevale; Barbara Marchesini; Michele Paternoster (Geochemistry, Geophysics, Geosystems)
Abstract Aiming at understanding the source of the fluids that mineralizing within seismically active fault zones, we investigate the noble gas isotopes (i.e., helium (He), neon (Ne), and argon (Ar)) in the fluid inclusions (FIs) trapped in the calcite veins sampled along high‐angle fault zones of the Contursi hydrothermal basin, southern Italy. The latter basin lies in close vicinity of the MW = 6.9, 1980 Irpinia earthquake and exposes numerous fault scarps dissecting Mesozoic shallow‐water carbonates. The analyses of noble gases (He, Ne, Ar) are conducted to identify the origin of the volatiles circulating along the faults at the time of calcite precipitation. Then, outcomes of this discussions are compared with currently outgassing of deep‐sourced CO2 coupled to mantle‐derived He in that area, whose output is larger than those from some volcanic areas worldwide. The results indicate that He in FIs is dominated by a crustal radiogenic component (4He), and by an up to 20% of a mantle‐derived component (3He), with a highest isotopic signature of 1.38 Ra. This value is consistent with the highest percentage of mantle‐derived He associated to high‐flux CO2 gas emission in the investigated area (1.41 Ra). We propose that the variability of the He isotopic signature measured in primary FIs can result from early trapping of fluid inclusions or post trapping processes and seismic activity that modify the pristine He isotopic signature (i.e., derived from the crust and/or mantle) in groundwater along the faults during periods of background seismicity. Such investigations are fundamental to understand fluid migration in fault systems and the role of fluids in processes of earthquake nucleation.